Preliminary Approach to Reimagining of Polluted Soil Ecosystem: Identification and Utilization of Autochthonous Hydrocarbon Degrading Bacteria - Otugboyega, JOSEPH; Otugboyega, OLAIDE OLUWAYEMISI; AYO, ITUNNU O.; ALIU, KAMORU T. (FUDMA Journal of Sciences, 2026)
Crude-oil Pollution negatively impacts the ecosystems. This study sought to recover crude-oil impacted soil ecosystem, by isolating, screening and identifying indigenous bacteria in a microcosm experiment. Samples of agricultural soil, were thoroughly blended with bonny light crude-oil and allowed to equilibrate for three weeks. Physiochemical parameters (pH, Moisture content, Electrical Conductivity, heavy metals, Polycyclic Aromatic Hydrocarbons (PAHs) and Total Petroleum Hydrocarbons (TPH) of the control and contaminated soils were assessed using standard laboratory methods and Gas Chromatography-Mass Spectrometry (GC-MS). Hydrocarbon-utilizing bacteria (HUB) were isolated from the impacted soil using Bacto Bushnell Haas broth supplemented with 1% crude-oil as the nutrient medium. Isolates’ Morphological, Biochemical and molecular characterization, as well as degradation screening were done. Physical parameters for the control and impacted soils differed significantly (P<0.05). The soil sample had a mean value of 47.5 x 109 cfu/ml count for Total Heterotrophic Bacteria. Bacteria isolates characterized, belonged to the genera; Klebsiella, staphylococcus, Enterobacter, Acinetobacter, Aeromonas and Kurthia. The population of HUB consisted Staphylococcus spp. (30%), Klebsiella spp. (20%), Aeronomas spp. (10%), Enterobacter spp., Acinetobacter spp. (10%), (10%) and Kurthia spp. (20%). Acinetobacter spp. showed the highest biodegradation capacity; with 2,6-dichlorophenol indophenols (DCPIP) indicator. Kurthia spp, a novel hydrocarbon degrader, was discovered. The study found that different isolates of native bacteria differ in degradation abilities and are effective for remediating polluted soils. The findings promote sustainable environmental management practices by harnessing naturally occurring bacteria for remediation, and supports the development of green technologies that align with global sustainability goals